2019
DOI: 10.1007/s13760-019-01148-w
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality and disability in stroke-associated pneumonia

Abstract: Whilst stroke-associated pneumonia (SAP) is common and associated with poor outcomes, less is known about the determinants of these adverse clinical outcomes in SAP. To identify the factors that influence mortality and morbidity in SAP. Data for patients with SAP (n = 854) were extracted from a regional Hospital Stroke Register in Norfolk, UK (2003-2015). SAP was defined as pneumonia occurring within 7 days of admission by the treating clinicians. Mutlivariable regression models were constructed to assess fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 24 publications
5
32
2
Order By: Relevance
“…33 In this study, stroke patients over the age of 65 had 6.3 times the risk of dying (AHR=6.3, 95% CI: 1.74-22.74) as those under the age of 45. This is similar to two studies conducted in Iran, 18,45 in United States, 52,53 UK, 40 Kenya, 43 older age was the predictors of mortality. The survival difference between young and older stroke Whereas study in Ethiopia 50,54 shows age has no association with mortality.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…33 In this study, stroke patients over the age of 65 had 6.3 times the risk of dying (AHR=6.3, 95% CI: 1.74-22.74) as those under the age of 45. This is similar to two studies conducted in Iran, 18,45 in United States, 52,53 UK, 40 Kenya, 43 older age was the predictors of mortality. The survival difference between young and older stroke Whereas study in Ethiopia 50,54 shows age has no association with mortality.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with a 15.7% survival rate in Finland, 39 a 37-month FHCSH survival rate after 36 months of follow-up, 39 thirty-seven month survival rate FHCSH after thirty-six follow-up, 37 and a month-long analysis and systematic review study in the United Kingdom. 40,41 But the survival rate of twelve months in this study is higher than the result reported (79.2%) in Lithuania, 42 59.3% in Kenya. 43 The disparity may be explained by the sample size difference, with inclusion criteria for an age range of 25-64 years in Lithuania and 719 study participants across three hospitals in Kenya, whereas our study is a single hospital-based study.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Recently, it was reported that elevated serum levels of CRP could be a predictor for post-stroke disability and prognosis (46) as well as a diagnostic marker for stroke-associated pneumonia (47,48). In the present study, median CRP serum levels were found to be significantly increased in pneumonia patients from the BL investigation timepoint, reaching a plateau at 48 h and decreasing again till the 120-h investigation.…”
Section: Immunological Datasupporting
confidence: 56%
“…Our study had some limitations that deserve comment. First, as a retrospective study, we cannot rule out the possibility that additional baseline variables (unmeasured confounders) might have some impact on the development of post-stroke pneumonia, such as dementia [31,32], the use of angiotensin receptor blockers or the use of angiotensin-converting enzyme inhibitors [33]. Second, the time course for post-stroke pneumonia was unclear.…”
Section: Discussionmentioning
confidence: 99%